2013
DOI: 10.1371/journal.pone.0054642
|View full text |Cite
|
Sign up to set email alerts
|

Blood Cues Induce Antipredator Behavior in Nile Tilapia Conspecifics

Abstract: In this study, we show that the fish Nile tilapia displays an antipredator response to chemical cues present in the blood of conspecifics. This is the first report of alarm response induced by blood-borne chemical cues in fish. There is a body of evidence showing that chemical cues from epidermal ‘club’ cells elicit an alarm reaction in fish. However, the chemical cues of these ‘club’ cells are restricted to certain species of fish. Thus, as a parsimonious explanation, we assume that an alarm response to blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 40 publications
(58 reference statements)
3
24
1
Order By: Relevance
“…It has been suggested that blood cues induce antipredator behavior in teleost fish (Barreto et al, 2013). In the present study we also showed that chemical cues present in the blood of conspecifics were able to moderately trigger the release of stress-related hormones (catecholamines, cortisol) ( Figure 1).…”
Section: Resultssupporting
confidence: 76%
“…It has been suggested that blood cues induce antipredator behavior in teleost fish (Barreto et al, 2013). In the present study we also showed that chemical cues present in the blood of conspecifics were able to moderately trigger the release of stress-related hormones (catecholamines, cortisol) ( Figure 1).…”
Section: Resultssupporting
confidence: 76%
“…Exposure to blood (5 mL, extracted from zebrafish and jundia ( Rhamdia quelen )—the use of jundia blood was due to the low yield of zebrafish blood extraction) was in a 10 L aquarium (Barreto et al, 2013); and exposure to alarm substance of conspecifics (Speedie & Gerlai, 2008) (1 mL, zebrafish) was in a 10 L aquarium (Barreto et al, 2010). After 15 min of exposure to each stressor, fish were captured, euthanized, and stored as described above (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Aquatic animals are also under strong selection pressure to accurately assess predation risk in a variety of contexts and evolve suitable morphological, behavioral, and life‐history traits (Brown, Rive, Ferrari, & Chivers, ; Chivers, Zhao, Brown, Marchant, & Ferrari, ; Ferrari, Messier, & Chivers, ; Helfman, ; Kepel & Scrosati, 2004; McCarthy & Fisher, ). However, in water, public information regarding predation risk often takes the form of damage‐released alarm cues; chemicals involuntarily leaked into the environment following injury that elicit antipredator responses in conspecifics (Acquistapace, Calamai, Hazlett, & Gherardi, ; Barreto et al., ; Chivers & Smith, ; Ferrari, Elvidge, Jackson, Chivers, & Brown, ; Kicklighter, Germann, Kamio, & Derby, ; Mathuru et al., ; Smith, ). Alarm cues are expressed by major aquatic taxa from both freshwater and marine environments, including echinoderms (Hagen, Anderson, & Stabell, ; Majer, Trigo, & Duarte, ), mollusks (Daleo et al., ; Dalesman, Rundle, & Cotton, ; Wood, Pennoyer, & Derby, ), crustaceans (Hazlett, ), arachnids (Persons, Walker, Rypstra, & Marshall, ), acarids (Grostal & Dicke, ), insects (Gall & Brodie, ; Llandres, Gonzálvez, & Rodríguez‐Gironés, ), and fishes (Brown, Ferrari, & Chivers, ).…”
Section: Introductionmentioning
confidence: 99%